PENGARUH TAX AVOIDANCE, BEBAN PAJAK TANGGUHAN, DAN LIABILITAS PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA RIIL (Studi empiris pada Perusahaan Manufaktur Sektor Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia tahun 2018 – 2023) - Deniar Fitri Andini; Haryanto Haryanto (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of tax avoidance, deferred tax liabilities, and deferred tax liabilities on real earnings management in manufacturing companies in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) during 2018-2023. This study uses real earnings management as the dependent variable proxied by abnormal operating cash flow, abnormal discretionary expenses, and abnormal production costs. The independent variables used in this study are tax avoidance, deferred tax expense and deferred tax liabilities. This study is also equipped with control variables consisting of investment opportunity sets and company size. The population of this study are non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) throughout 2018 - 2023. By using purposive sampling method, 126 observations were obtained. The statistical tests used are descriptive statistical tests, classical assumption tests (normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests), and hypothesis tests (simultaneous significance tests (F tests), individual parameter tests (T tests), and coefficient of determination tests (R2)).The results showed that tax avoidance significantly positively affects real earnings management through abnormal operating cash flow, abnormal discretionary expenses, and abnormal production costs. Deferred tax expense can significantly positively affect real earnings management through abnormal operating cash flow, abnormal discretionary expenses, and abnormal production costs. The research findings also show that deferred tax liabilities have not been able to positively influence real earnings management through abnormal operating cash flow, abnormal discretionary expenses and abnormal production costs.